Managers' Roles in Performance-Based Reward Enhancing Employees’ Feelings of Procedural Justice - Azman Ismail; Mohd Ridwan Abd Razak (KINERJA, 2017)
This study assesses the correlation between managers’ roles in performance based reward and procedural justice at disaster agencies in Malaysia. The outcomes of SmartPLS (PLS-SEM) path model analysis demonstrated that the capability of management to correctly apply communication, involvement and performance assessment in performance-based reward could lead to higher employees' feelings of procedural justice in the organizational sample. Further, this study offers discussion, implications, and conclusion.Keywords: Managers’ roles, performance based reward, procedural justice, SmartPLS